UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM (PAI) DI SMA NEGERI 4 PAGARALAM - Marhan Marhan (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: This study aims to determine the leadership of the principal, teacher performance of Islamic Education (PAI), and the efforts of the leadership of principals on teacher performance of Islamic Education (PAI) at SMAN 4 Pagaralam. The method used in this research is qualitative method which the research methods used to examine the condition of natural objects by researchers as a key instrument. While data collection techniques through observation, interviews, and documentation. Based on the results of research and discussion in mind that school leadership SMAN 4 Pagaralam is a type of democratic leadership, which means a good leader for the group, realized that his job was to coordinate the work and duties of all members with a sense of responsibility, be aware that the strength of the organization depends on the participation active every member wants to hear opinions and suggestions and even criticism from subordinates, always consulted with teachers about the actions and decisions proposed / desired by the leadership, trying to give a boost to participate actively implementing all decisions and activities that have been set. Islamic religious education teacher performance based assessment of school heads have not been able to choose the method of learning is good and appropriate in the learning process, not too precise deliver learning content, and in developing learning programs that include annual program, the semester program, lesson plan (RPP), Islamic religious education teachers lack the ability to put together a program of learning. Efforts were made more active principals to foster and enhance the competence and performance of teachers in the school principal sent teachers participated in the training, upgrading courses, workshops, workshops and seminars. Principals conduct training and socialization of the results of government policies, and even bring in speakers who are competent, motivated teachers PAI to continue their education to a higher level, conduct comparative studies to other, more advanced school with the teachers and other school community, complete infrastructure and supporting media credible form of learning, giving awards to teachers who excel and perform well.